Penerapan Permainan Talking Stick dalam pembelajaran keterampilan membaca pada siswa kelas 12 di MAN 8 Jombang - Putri Dyah Fortuna; Abdul Ghofur (JOURNAL SAINS STUDENT RESEARCH, 2025)
Lack of interest in reading, limited vocabulary, and low confidence in reading Arabic texts are the background of this study. Reading skills are an important aspect of Arabic language learning that requires mastery of pronunciation, vocabulary, and text comprehension. The “Talking Stick” method is a game-based strategy involving a relay stick that is given alternately to students as music is played. The student holding the stick when the music stops must read a designated section of text. This study examines: (1) the application of this method in reading learning, (2) the improvement of reading ability of grade XII students after the application of this method, and (3) the supporting and inhibiting factors. The approach used was descriptive qualitative with observation, interview, and documentation techniques. The results showed that this method improved students' focus, readiness, and participation in reading. Students' reading skills improved, characterized by courage and clarity of pronunciation. Supporting factors include teacher readiness, conducive classroom atmosphere, and student enthusiasm, while the main obstacles are differences in reading ability and time constraints. This research contributes to the development of Arabic learning strategies that are more interesting and in accordance with the needs of learners